Prognostic role of serum C-reactive protein in carcinoma oesophagus - Gupta, Arun; Dall, Tejinder Singh; Bansal, Darpan (International Surgery Journal, 2019)
Background: Oesophageal cancer (EC) is the eighth most common cancer around the world. EC incidence and mortality are affected by geography. Eastern Asia, eastern and southern Africa has the highest rates, whereas Europe and North America show lower rates. Methods: The study was conducted on 30 cases of EC diagnosed in Sri Guru Ram Das Institute of Medical Sciences and Research, Sri Amritsar. The study was carried during period starting from January 2017 to June 2018. Serum C - reactive protein levels measurement was made in addition to the other routine investigations. Results: The sample consisted of 30 patients presenting with EC. Total number of males was 7 (23.33%) and there were 23 (76.66%) females. It was found in present study that the most common age group presenting with oesophageal cancer was 41-60 years followed by 61-80 years. It was also observed in the present study that majority of patients 15 (50%) were housewives. It was also observed that 17 (56.67%) of patients had more than 6 mg/l level of preoperative C-reactive proteins. Among the poorly differentiated histological grade patients 14 (73.68%) had high level of C-reactive proteins. Moreover hospital stay was also more among the patients having high pre-operative levels of C-reactive proteins (CRPs). Conclusions: The prognosis for patients with preoperative serum elevation of CRP was significantly more unfavourable than that for patients without serum CRP elevation.